Advances in preclinical and clinical studies of oncolytic virus combination therapy - Du, Wenlong; Na, Jintong; Zhong, Liping; Zhang, Pumin (Frontiers in Oncology, 2025)
Oncolytic viruses represent a distinct class of viruses that selectively infect and destroy tumor cells while sparing normal cells. Despite their potential, oncolytic viruses encounter several challenges as standalone therapies. Consequently, the combination of oncolytic viruses with other therapeutic modalities has emerged as a prominent research focus. This paper summarizes the tumor-killing mechanisms of oncolytic viruses, explores their integration with radiotherapy, chemotherapy, immune checkpoint inhibitors, CAR-T, and CAR-NK therapies, and provides an overview of related clinical trials. By synthesizing these advancements, this study seeks to offer valuable insights for the clinical translation of oncolytic virus combination therapies.